English Medium Instruction in Secondary Education: Insights from a Private Bilingual School in Pontianak - Paulina Erawati Paramita (Journal on Education, 2025)
The adoption of English as a Medium of Instruction (EMI) is a growing trend in Indonesian education. This study investigates the implementation of EMI and students' perceptions at a private bilingual junior high school in Pontianak. A descriptive survey design was employed, with data collected through a questionnaire from 44 ninth-grade students. The findings reveal a significant discrepancy: students hold overwhelmingly positive perceptions of EMI's value for their future and their English skill development. However, data indicates a clear inconsistency in implementation. Teachers of non-language subjects (Biology, Mathematics, Physics) frequently use Bahasa Indonesia in the classroom, while the English teacher consistently uses English. The study concludes that while students are positively disposed towards and feel capable of learning via EMI, the teachers of content subjects are not fully implementing it. This suggests a gap between policy and practice, highlighting a need for targeted teacher support and training to ensure the effective execution of the school's bilingual program.